2017
DOI: 10.18608/jla.2017.41.6
|View full text |Cite
|
Sign up to set email alerts
|

Role Modelling in MOOC Discussion Forums

Abstract: ABSTRACT:To further develop rich and expressive ways of modelling roles of contributors in discussion forums of online courses, particularly in MOOCs, networks of forum users are analyzed based on the relations of information-giving and information-seeking. Specific connection patterns that appear in the information exchange networks of forum users are used to characterize user roles. Additionally, semantic roles are derived by identifying thematic areas in which an actor (learner) looks for information (probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…As for forums, they represent an environment of interaction among course learners, where the analysis of information‐giving and information‐seeking relations are taken into account for modeling contributor roles. In this sense, Hecking, Chounta, and Ulrich () generate connection patterns from information exchange networks to identify user roles. Inclusive, they produce semantic roles by identifying topics where a learner seeks information and the areas of interest in which a learner shares information with others.…”
Section: Underlying Factorsmentioning
confidence: 99%
“…As for forums, they represent an environment of interaction among course learners, where the analysis of information‐giving and information‐seeking relations are taken into account for modeling contributor roles. In this sense, Hecking, Chounta, and Ulrich () generate connection patterns from information exchange networks to identify user roles. Inclusive, they produce semantic roles by identifying topics where a learner seeks information and the areas of interest in which a learner shares information with others.…”
Section: Underlying Factorsmentioning
confidence: 99%
“…Indeed, it could be corroborated that peer-to-peer learning support was beneficial for both helpers and helpees. Along similar lines, Hecking et al (2017) studied the dynamics of learner profiles in MOOC ("Massive Open Online Courses") forums identifying specific combinations of social role patterns and thematic interactions (help seeking/giving related to certain topics). In the discussion of their findings, already Bull et al (2001) indicated that forming small learning groups with specific task assignments in larger online courses should be beneficial for stimulating engagement and collaborative knowledge building.…”
Section: Introductionmentioning
confidence: 99%
“…taking advantage of systems properties to superficially complete the task) [4]. Another stream of work looks at detecting engagement aspects that can be linked to cognition, such as zoning out and mind wandering [5,12], and information seeking/giving [14]. Thirdly, the affective response to instructions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We build on the ICAP framework [8] to link cognitive engagement activities to observable behaviors. While ICAP has been used to categorize information seeking in MOOC forums [14,27], its adoption for analyzing video engagement is novel. In our adoption, we have shifted the focus from behavioral aspects derived from interaction log files (e.g.…”
Section: Introductionmentioning
confidence: 99%